Linguistic means of valuation and assessment: A systemic-functional analysis of press coverage of February 24, 2022 - Pawliszko, Judyta (Papers in Linguistics, 2025)
The aim of the article is to characterize the ways of presenting events of February 24, 2022 directly and indirectly related to the Russian-Ukrainian war in The New York Times and The Moscow Times. Based on case studies, the article describes how the signals of valuing emotions, behaviours, actions, and attitudes were encoded in the research material. The systemic-functional analysis of discourse (SFAD) methodology is applied to identify linguistic means of assessing and negotiating attitudes which are used by the authors of both articles and stem from the grammatical system of their respective languages. Analysis of registers assigned to specific research categories (affect, judgement, appreciation) revealed that the press accounts of 24 February 2022 are dominated by grammatical constructions with the verb as the key element organising the system of interpersonal meanings, especially in the context of assessing and negotiating attitudes. The final conclusions of the study suggest that predicative expressions in newspaper articles are more powerful than expressions of appreciation.